Evaluation of Soil Parameters After Long-Term Subsurface Drip Irrigation Under Minimum Tillage System - E. B. Rutter; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this study was to evaluate soil parameters after the long-term use of sub-surface drip irrigation under no-till, with the use of high pH irrigation water. Results from this study showed that stratification of soil pH and soil test phosphorus (P) was more prominent when compared to other soil parameters. However, the stratification of pH and soil test P is likely the combined effect of surface fertilizer application and sub-surface irrigation water. The stratification of other parameters, such as soil calcium (Ca) and sodium (Na) and electrical conductivity (EC), was less clear. Soil test potassium (K) showed some level of stratification, with higher levels deeper in the soil profile; this is likely due to some K application through the irrigation water, but also the finer textured soil.
Keywords: drip irrigation; calcium; sodium; pH